An application of extreme value theory in estimating liquidity risk - Sonia Benito Muela; Carmen López Martín; Raquel Arguedas Sanz (European Research on Management and Business Economics (ERMBE), 2017)
The last global financial crisis (2007–2008) has highlighted the weaknesses of value at risk (VaR) as ameasure of market risk, as this metric by itself does not take liquidity risk into account. To address this problem, the academic literature has proposed incorporating liquidity risk into estimations of market risk by adding the VaR of the spread to the risk price. The parametric model is the standard approach used to estimate liquidity risk. As this approach does not generate reliable VaR estimates, we propose estimating liquidity risk using more sophisticated models based on extreme value theory (EVT). We find that the approach based on conditional extreme value theory outperforms the standard approach in terms ofaccurate VaR estimates and the market risk capital requirements of the Basel Capital Accord.
Keywords: G32; C14; C22; C53; 650; Value-at-risk; Liquidity risk; Extreme value theory; Basel capital accord